2007
DOI: 10.1103/physreva.76.013603
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-symmetry localized modes and breathers in binary mixtures of Bose-Einstein condensates in optical lattices

Abstract: We study localized modes in binary mixtures of Bose-Einstein condensates embedded in onedimensional optical lattices. We report a diversity of asymmetric modes and investigate their dynamics. We concentrate on the cases where one of the components is dominant, i.e. has much larger number of atoms than the other one, and where both components have the numbers of atoms of the same order but different symmetries. In the first case we propose a method of systematic obtaining the modes, considering the "small" comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 32 publications
(36 reference statements)
0
31
0
Order By: Relevance
“…The existence of dark-bright states of binary BECs mixtures was demonstrated in [15]. On the other hand, the existence of localized states of different symmetry type (mixed symmetry states) was numerically and analytically demonstrated in [16]. Properties of coupled gap solitons in binary BECs mixtures with repulsive interactions were also analyzed in the multidimensional case [17] as well as for combined linear and nonlinear optical lattices [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of dark-bright states of binary BECs mixtures was demonstrated in [15]. On the other hand, the existence of localized states of different symmetry type (mixed symmetry states) was numerically and analytically demonstrated in [16]. Properties of coupled gap solitons in binary BECs mixtures with repulsive interactions were also analyzed in the multidimensional case [17] as well as for combined linear and nonlinear optical lattices [18].…”
Section: Introductionmentioning
confidence: 99%
“…Properties of coupled gap solitons in binary BECs mixtures with repulsive interactions were also analyzed in the multidimensional case [17] as well as for combined linear and nonlinear optical lattices [18]. Although gap-soliton breathers of multicomponent GPE involving periodic oscillations of the two components densities localized on adjacent sites of an optical lattice have been found [16] (in analogy to what was done for single component case in [6], such states can also be seen as matter wave realizations of Josephson junctions), no much numerical and theoretical study has been done until now on AJJ of binary mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Two-site B-B compactons also exist and, similarly to discrete breathers of binary non linear lattices [24], can be of three types: in-phase, out-of-phase and mixed-symmetry type, e.g. with both components symmetric (in-phase), or with both anti-symmetric (out-of phase), or with one component symmetric and the other anti-symmetric (mixedsymmetry) [24], with respect to the middle point between the two sites on which they are localized, respectively.…”
Section: Two-site Compactonsmentioning
confidence: 99%
“…with both components symmetric (in-phase), or with both anti-symmetric (out-of phase), or with one component symmetric and the other anti-symmetric (mixedsymmetry) [24], with respect to the middle point between the two sites on which they are localized, respectively. Two-site B-B compactons directly follow from Eqs.…”
Section: Two-site Compactonsmentioning
confidence: 99%
“…These studies demonstrated that the stationary state of a BEC mixture depends critically on the intra-and inter-species scattering lengths, as does its stability against excitations [23][24][25][26]. Additional aspects examined involved the static and dynamic properties [27][28][29][30][31], including the excitation spectrum and the nature of low-frequency simultaneous collective excitations, and solitary waves [32][33][34][35][36] (see also references therein).…”
Section: Introductionmentioning
confidence: 99%